Modeling of drying kinetics and chemical analysis for optimal preservation of pitahaya, aguaymanto and pineapple fruits using a parabolic solar dehydrator in the Amazon region - Peru - Merbelita Yalta Chappa; Wildor Gosgot Angeles; Luz Quispe-Sanchez; Diana Carina Mori Servan; Homar Santillan Gomez; Manuel Oliva-Cruz; Miguel Ángel Barrena Gurbillón (Journal of Agriculture and Food Research)
Fruits that were not efficiently dehydrated favor the growth of microorganisms and facilitate chemical reactions that can alter their quality and storage standards. In this research, the drying kinetics were modeled, and a chemical analysis was performed to determine the optimum preservation conditions for pitahaya (Selenicereus undatus), aguaymanto (Physalis peruviana), and pineapple (Ananas comosus) fruits using a parabolic solar dehydrator in the Amazon region of Peru. Five mathematical models were used to determine the drying curve, with the criterion of selection the best model with the coefficient of determination (R2) and model efficiency (EF); in addition, pH and titratable acidity were evaluated during the dehydration period. The results revealed that the Midilli model fitted best for pitahaya (R2 = 0.9995, EF = 0.999) and aguaymanto (R2 = 0.9965, EF = 0.993); however, for pineapple slices, the most relevant model was Weibull (R2 = 0.9998, EF = 0.999). In the chemical analysis evaluation, it was evident that as time went by, the pH increased and the titratable acidity decreased; the fruit with the highest pH when reaching its optimum dehydration point was the pitahaya (5.98); it also indicated the lowest titratable acidity (0.0010 %). On the other hand, the lowest pH values were observed in aguaymanto (4.01) and pineapple (4.00), with titratable acidity values ranging from 0.0955 % to 0.0985 % respectively. This study states that the parabolic solar dehydrator is effective for optimal pitahaya, aguaymanto, and pineapple preservation, aligning perfectly with the Midilli and Weibull kinetic models while maintaining quality standards.